A magnetorheological flap valve micropump for drug delivery applications. (March 2023) - Cesmeci, Sevki; Hassan, Rubayet; Baniasadi, Mahmoud; Palacio, Anthony G
In this paper, we propose a flap valve micro-fluidic pump that relies on an electromagnetic actuation mechanism. We employed a multiphysics-based simulation methodology to prove the proposed concept. More specifically, the complex and fully coupled magneto-solid-fluid interaction analyses were carried out via a two-dimensional, time-dependent computational model to determine the deformation of the upper wall of the pump chamber and the velocity field inside the pump channel. The simulations were performed in COMSOL Multiphysics software. The simulation approach was verified through a validity check study by replicating an existing study in the literature. Once verified, the full simulations were performed for the proposed concept. The performance characteristics of the pump were presented and discussed. In addition, a parametric study was conducted to see the effects of important design parameters on the net pumped volume, results of which were also presented and discussed. The proposed micropump can transfer 1.9 µL of fluid in one pumping cycle, which is almost two times the other micropump models. Also, the proposed flap valve can reduce the backflow up to 10 times during the expansion phase in comparison with the no valve model. The parametric studies demonstrated that the net pumped volume of the fluid is directly proportional to the channel height and valve spacing distance and is inversely proportional to the upper wall thickness, elastic modulus of the pump structure, width, height, and Poisson ratio of the valves. The proposed micropump could potentially be used in a broad range of applications, such as an insulin dosing system for Type 1 Diabetic patients, artificial organs to transport blood, organ-on-chip applications, and so on.